Insights from Qur’anic Stories and Parables QSP for Al-Qur’an Engagement Methods QEM; the Naqli-Aqli Integration Boost - Kirembwe Rashid Abdul Hamed; Mohd Aderi Che Noh; Siti Rosilawati Ramlan; Mohammad Najib Jaffar; Sakinah Ahmad; Hayati binti Ismail; Maziahtusima Ishak; Mardhiah Yahaya; Sarifah Nurhanum Syed Sahuri (Tazkiyyah Global Enterprise, 2025)
Non-Indexed Publication